Emotional Branding Strategy in Building Brand Loyalty of Local Fashion Consumers: The Role of Brand Humanization, Emotional Connection, and Brand Personality - Azhari, Azlan (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2026)
This study aims to examine the influence of brand humanization, emotional connection, and brand personality on brand loyalty in Erigo fashion products. Erigo as a local Indonesian brand that is growing rapidly in the fashion industry has demonstrated innovative marketing strategies in building emotional engagement with its consumers. The sample of this study consisted of 100 Erigo consumers aged 18-40 years and from Makassar City. Data were collected through an online questionnaire using a 5-point Likert scale. The data analysis technique used Multiple Linear Regression Analysis with the support of SPSS software version 24. The results showed that the three independent variables (brand humanization, emotional connection, and brand personality) had a significant and positive effect on Erigo brand loyalty both partially and simultaneously. Brand humanization showed the strongest influence with a coefficient of 0.424 (p < 0.001), followed by brand personality with a coefficient of 0.320 (p < 0.001), and emotional connection with a coefficient of 0.168 (p < 0.001). The R-square value of 0.548 indicates that the three variables can explain 54.8% of the variability in Erigo's brand loyalty. This finding provides important implications for Erigo's management in optimizing its marketing strategy by strengthening the brand's human dimension, creating authentic emotional connections, and communicating a consistent and relatable brand personality to the target market.